PELAKSANAAN PEMBELAJARAN BAHASA INDONESIA PADA MASA PANDEMI COVID-19 DI SMPN 2 SATU ATAP TANGARAN KABUPATEN SAMBAS - Indah kurniasari; Abdussamad Abdussamad; Agus Wartiningsih (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research is a study on learning that was conducted face-to-face limited during the Covid-19 pandemic.The learning process during the pandemic has undergone many changes, especially in the allocation of learning time. The problem raised in this research is the learning process of Indonesia Language which includes planning, implementation and assessment. This study uses qualitative descriptive methods. The data in this study is sourced from Indonesian teachers in grade 8th. Based on the results of the planning analysis, the implementation and assessment of learning can be known that in the learning implementation plan made by the teacher has a complete component so as to reflect the essence of the learning process. Furthermore, in the process of implementing learning teachers and students experience difficulties, namely limited social interaction and limited learning time. Lastly, the assessment of learning conducted by teachers is knowledge assessment and skills assessment. Knowledge assessment is conducted in the school, and the skills assessment is given in the form of incomplete work done in the school which will then be continued at home.Keywords: Learning, Covid-19, face-to-face limited